Covid-19 Patient Condition at Early Pandemic in Jakarta - Andika Chandra Putra; Wiwien Heru Wiyono; Mohammad Fahmi Alatas; Aulya Fairuz; Fransiska Fransiska; Bettia Bermawi; Ratna Moniqa; Hendra Koncoro; Laurentius Aswin Pramono; Maria Edith Sulistio; Ramzi Ramzi; Robert Sinto; Rachmat Hamonangan; C. Krismini Dwi Irianti; JB Endrotomo Sumargono (Jurnal Respirologi Indonesia, 2021)
Background: COVID-19 is a disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) that has become a pandemic. It became apparent that COVID-19 transmitting from person to person. The clinical manifestations and characteristics of COVID-19 encompassing from asymptomatic infection until severe pneumonia and death. This study aimed to describe and compare the characteristics between COVID-19 suspected patients and confirmed patients at an early pandemic in Jakarta, Indonesia. Methods: A cross-sectional design was used in this study. Data were collected from March to April 2020 using the electronic health record reporting database, initial laboratory tests, and RT-PCR for SARS-CoV-2 results. There were 58 subjects: 43 COVID-19 confirmed patients and 15 COVID-19 suspected patients. Results: Male was found predominantly in COVID-19 confirmed patients than female. The mean age of confirmed patients was 49,6 years old. Nearly half of the confirmed patients had comorbidities namely hypertension and diabetes mellitus. Fever and cough were the most common presenting symptoms, and they were also found in suspected patients. Confirmed patients tended to have lymphopenia and neutrophilia. Pulmonary infiltrate was the most common feature in both confirmed and suspected patients. Conclusion: There were no significant differences found between COVID-19 confirmed and suspected cases regarding demographic characteristics, comorbidities, presenting symptoms, physical examination results, laboratory tests, and chest x-ray results. COVID-19 confirmed patients had a history of exposure to COVID-19 confirmed patients.